Neuroendocrine pathogenesis of perimenopausal depression - Han, Yuping; Gu, Simeng; Li, Yumeng; Qian, Xin; Wang, Fushun; Huang, Jason H. (Frontiers in Psychiatry, 2023)
With the development of social economics and the increase of working pressure, more and more women are suffering from long-term serious stress and showing symptoms of perimenopausal depression (PMD). The incidence rate of PMD is increasing, and the physical and mental health are seriously affected. However, due to the lack of accurate knowledge of pathophysiology, its diagnosis and treatment cannot be accurately executed. This article summarizes recent advances about the etiology as well as the diagnosis and treatment of PMD, trying to elaborate the stress induced neuroendocrine changes and endocrine mechanism for PMD. In addition, we also summarized the latest progress of treatment by reviewing relevant literature on the neuroendocrine pathogenesis and treatment of PMD. The purpose is to probe into new ways of treatment of PMD by reviewing new studies about the neuroendocrine mechanism and treatment of PMD.